DETERMINANTS OF ANEMIA AMONG THIRD TRIMESTER PREGNANT WOMEN - Rosa Susanti; Okta Zenita Siti Fatimah; Wanti Astriani Hasan; Seventina Nurul Hidayah (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
The Indonesian Health Survey (SKI) 2023 revealed that 27.7% of pregnant women suffered from anemia. Data from the Larangan Utara Public Health Center (UPT Puskesmas) in Tangerang City indicated an upward trend in anemia cases among women in their third trimester of pregnancy. In 2022, anemia was identified in 122 women (13.7%) out of 887 who were examined for hemoglobin levels, and the number increased to 135 women (15.5%) out of 867 in 2023. This study aimed to determine the primary factors contributing to anemia among third-trimester pregnant women at the Larangan Utara Public Health Center, Tangerang City, in 2024. The research adopted a quantitative approach with a logistic regression design. A total of 60 respondents were included through a total sampling technique. Data collection was conducted using a structured questionnaire, and analysis was performed using multivariate linear regression. The findings indicated that three main factors were significantly associated with anemia: Chronic Energy Deficiency (CED) (p = 0.000), educational level (p = 0.031), and compliance with iron (Fe) tablet intake (p = 0.035). Among these, Chronic Energy Deficiency was identified as the most dominant factor influencing anemia occurrence. In conclusion, anemia among third-trimester pregnant women is influenced by chronic energy deficiency, educational level, and adherence to Fe tablet consumption, with CED being the most significant determinant. It is recommended that healthcare providers at the Larangan Utara Public Health Center implement more effective prevention and management strategies, including nutrition education, infection control, and enhanced monitoring for high-risk pregnant women.